2009
DOI: 10.1111/j.1365-2486.2009.02003.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to preindustrial, current and future atmospheric CO2 and temperature differentially affects growth and photosynthesis in Eucalyptus

Abstract: To investigate if Eucalyptus species have responded to industrial-age climate change, and how they may respond to a future climate, we measured growth and physiology of fast-(E. saligna) and slow-growing (E. sideroxylon) seedlings exposed to preindustrial (290), current (400) or projected (650 lL L À1 ) CO 2 concentration ([CO 2 ]) and to current or projected (current 1 4 1C) temperature. To evaluate maximum potential treatment responses, plants were grown with nonlimiting soil moisture. We found that: (1) E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
107
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(119 citation statements)
references
References 68 publications
10
107
2
Order By: Relevance
“…Recently, it was suggested that eucalypts could make a large contribution to carbon sequestration in a future greenhouse world, based on a demonstrated positive growth response to an elevation of either atmospheric CO 2 or temperature 33 . Our results independently predict that eucalypt forests and woodlands could be a superior long-term carbon bank compared with climatically similar fire-dependent biomes in other continents.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was suggested that eucalypts could make a large contribution to carbon sequestration in a future greenhouse world, based on a demonstrated positive growth response to an elevation of either atmospheric CO 2 or temperature 33 . Our results independently predict that eucalypt forests and woodlands could be a superior long-term carbon bank compared with climatically similar fire-dependent biomes in other continents.…”
Section: Discussionmentioning
confidence: 99%
“…Results from previous studies on the effects of climate change on nitrogen cycling are mainly focused on soil enzymatic activities, nitrogen dynamics, and aboveground plant properties (Ghannoum et al, 2010;Rütting et al, 2010;Van Groenigen et al, 2011;Dijkstra et al, 2012), with less understanding of the belowground microbial communities Pereira et al, 2011Pereira et al, , 2013Rousk et al, 2012;Zhou et al, 2012). Meanwhile, emerging biogeochemical process-based models are attempting to directly link microbial physiology with soil nutrient cycling (Frey et al, 2013), but they are facing difficulties of integrating and parameterizing less-understood microbial dynamics into modelling effort.…”
Section: Elevated Temperature Has More Important Roles Than Elevated mentioning
confidence: 99%
“…In the meantime, the atmospheric CO 2 concentrations have increased by 40% since the pre-industrial times to current levels of >400 ppm, primarily from fossil fuel combustion and landuse changes (IPCC, 2013). These global climate changes are expected to have direct consequences on aboveground plant communities (Ghannoum et al, 2010), or indirectly influence the net primary production (NPP) by enhancing the nutrient competition between plants and microorganisms (Rütting et al, 2010) and altering the microbial turnover rates of soil nutrients (Karhu et al, 2014). The elevated CO 2 could enhance the NPP of Earth's ecosystems to increase carbon and nitrogen sequestration in soil organic matter and plant biomass, which in the long term may drive progressive nitrogen limitation of natural settings (Luo et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photosynthetic responses to elevated CO 2 concentrations have been widely studied during the past decades (Wang et al 1995;Curtis et al 2000;Ghannoum et al 2010). The effects of elevated CO 2 concentration on photosynthesis were found to be dependent on plant species, environmental conditions, duration of CO 2 exposure, and growth stage of plants (Tissue et al 1997;Ainsworth et al 2002;Sigurdsson et al 2002;Aranjuelo et al 2009).…”
Section: Introductionmentioning
confidence: 99%